1996
DOI: 10.1002/(sici)1096-9861(19960805)371:4<589::aid-cne8>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of glycine-immunoreactive profiles in the monkey spinal cord: A light microscopic and ultrastructural study

Abstract: The present study analyzed the relationships of glycine (GLY)-immunoreactive (-IR) and unlabeled profiles in the primate spinal cord. Light microscopic analysis demonstrated GLY-IR profiles in laminae III-VII, with fewer labeled profiles in laminae I, II, VIII, IX and X. The dorsal part of the lateral funiculus and the dorsal funiculus contained few labeled axons, in contrast to all other areas of white matter, which were heavily labeled. At the electron microscopic level, GLY-IR terminals in monkeys contained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…High concentrations of neurotransmitter such as GABA and glycine are also present in a sub-population of mature WM axons in several species (Carlton et al, 1996;Davanger et al, 1991;Rogers and Pow, 1995;Todd and Sullivan, 1990;van den Pol and Gorcs, 1988;Wilson et al, 1996). Block of GABA uptake mimics the effects of GABA upon axon conduction in the neonatal rat optic nerve (Sakatani et al, 1991), while block of catecholamine uptake mimics the effect of nor-adrenaline (Nikolaeva et al, 2009); observations consistent with tonic operation of functional neurotransmitter uptake in the tissue.…”
Section: Gaba and Glycinementioning
confidence: 60%
See 1 more Smart Citation
“…High concentrations of neurotransmitter such as GABA and glycine are also present in a sub-population of mature WM axons in several species (Carlton et al, 1996;Davanger et al, 1991;Rogers and Pow, 1995;Todd and Sullivan, 1990;van den Pol and Gorcs, 1988;Wilson et al, 1996). Block of GABA uptake mimics the effects of GABA upon axon conduction in the neonatal rat optic nerve (Sakatani et al, 1991), while block of catecholamine uptake mimics the effect of nor-adrenaline (Nikolaeva et al, 2009); observations consistent with tonic operation of functional neurotransmitter uptake in the tissue.…”
Section: Gaba and Glycinementioning
confidence: 60%
“…GABA is localized in neonatal rat optic nerve glia, with expression down-regulated with maturation (Ochi et al, 1993;Sakatani et al, 1992), although this may be due to increased rates of GABA degradation since numerous GABA1 WM astrocytes are apparent in adult rat following inhibition of the catabolic enzyme GABA-alpha-ketoglutaric acid aminotransferase (Bull and Blomqvist, 1991). High concentrations of neurotransmitter such as GABA and glycine are also present in a sub-population of mature WM axons in several species (Carlton et al, 1996;Davanger et al, 1991;Rogers and Pow, 1995;Todd and Sullivan, 1990;van den Pol and Gorcs, 1988;Wilson et al, 1996).…”
Section: Gaba and Glycinementioning
confidence: 99%
“…Afferent terminals may therefore act directly on GABAergic interneurones mediating PAD (Zou et al, 2001). GABA‐like immunoreactivity (albeit often rather weak) has frequently been reported in dendrites postsynaptic to the central terminals of glomeruli in laminae I and II (Carlton and Hayes, 1990; Todd and Lochhead, 1990; Carlton et al, 1996; Todd, 1996) and to intracellularly labelled C and Aδ fibres (Alvarez et al, 1992, 1993; Bernardi et al, 1995). Only rarely did we see this in dendrites postsynaptic to hair follicle afferents, and immunoreactivity for GABA has not been reported by other immunohistochemical studies of physiologically identified Aα or Aβ fibres such as hair follicle afferents (Maxwell and Noble, 1987), type Ia or type II muscle spindle afferents (Maxwell et al, 1990; Maxwell and Riddell, 1999; Watson and Bazzaz, 2001), slowly adapting periodontal afferents (Bae et al, 1997), or for terminals of large‐diameter myelinated afferents labelled by retrograde transport of Cholera toxin B (Bae et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The PBil receives afferents predominantly from the spinal cord, in particular from the lateral reticulated area and the lateral spinal nucleus (Feil and Herbert 1995). However, these spinal areas apparently contain no glycinergic neurons (Todd and Sullivan 1990;Carlton et al 1996). The possibility remains that the glycinergic input to the PBil originates laterally in the medullary reticular formation that has recently been shown to project also to the PBil (Feil and Herbert 1996) and that contains glycinergic neurons in abundance (Rampon et al 1996).…”
Section: Glycinementioning
confidence: 99%